Exploring Students’ Participation in English Classrooms in Higher Education - Dwi Titi Maesaroh; Ade Irawan (Journal of English in Academic and Professional Communication, 2026)
Students’ class participation is essential in English learning, as it facilitates improvement in language proficiency. This study aims to explore how students self-assess their class participation and to ascertain the key determinants that deter students’ active engagement in classroom activities at the higher education level. This study employed a mixed-method research design to investigate university students’ perceptions and self-assessments of their participation in English language classrooms, involving 22 respondents within a single classroom setting. Data was collected through closed-ended and open-ended questionnaires.  The results highlight notable barriers to in-class participation, including personal issues such as transportation to class, anxiety about asking or responding to questions, and limited English proficiency.  The results also show how crucial a supportive environment, well-prepared lectures, and group discussions during learning are for encouraging participation. This study sheds light on how students engage in class and what motivates them to be active or passive participants, both for English teachers and lecturers.